Analyzing Research Trends on High Intensity Interval Training and Oxidative Stress: A Bibliometric Analysis (2000-2023) - Anshul Meena; Pradeep Singh Chahar; Jagdeep Singh (Physical Education Theory and Methodology)
Background. Exercise-induced oxidative stress, often resulting from high-intensity interval training (HIIT), can cause short-term declines in performance due to alterations in cellular and DNA function. Therefore, oxidative stress markers have gained increased attention for their potential role in reducing risks and improving individual performance.